Diagnosis and Monitoring of Acute Infections with Emphasis on the Novel Biomarker Human Neutrophil Lipocalin. (23rd October 2019) - Venge, Per; Xu, Shengyuan
Abstract: Background: Acute infections affect all of us at least once or twice a year. Sometimes the infection prompts a visit to our doctor, and the question asked by the patient and the doctor is whether the infection should be treated with antibiotics or not. This is an important question because unnecessary prescription of antibiotics adds to the increasing problem of antibiotics resistance. Objective means to determine whether the infection is caused by bacteria or virus, therefore, are necessary tools for the doctor. Content: White blood cell counts, C-reactive protein, and other acute-phase reactants in blood are important tools and are commonly used, but unfortunately lack in sensitivity and specificity. In this review we describe some novel biomarkers with increased clinical performance in this regard. The superior biomarker is human neutrophil lipocalin (HNL), a protein released from activated blood neutrophils. HNL may be measured in serum, plasma, or in whole blood after activation with a neutrophil activator. The diagnostic accuracy in the distinction between bacterial and viral acute infections was shown to be in the range of 90%–95% when measured in serum or activated whole blood. Summary: A point-of-care assay for the measurement of HNL in whole blood is currently being developed, which will allow the diagnosis of acute infections within 5–10 min. For certain indications, HNL measurement may be complemented by 1 or 2 other biomarkers, which may increase the diagnostic discrimination between bacterial and viral infections even further.